THE TRANSLATION OF ENGLISH POLITE REQUESTS INTO BAHDINI KURDISH - Mohamed, Dara; Sigar, Ahmed Hayder (Humanities Journal of University of Zakho, 2026)
Politeness refers to the social norms and behaviours that imply respect, consideration and courtesy towards others. The current study investigates the translation of polite requests as speech acts from English into Kurdish. Focusing on the challenge of translating pragmatic meaning, it aims at identifying the different patterns of polite requests in English, translating these patterns from English into Kurdish to see how they are realized in Kurdish and shedding light on the points of similarity and difference between the English constructions and their realizations in Kurdish. In order to achieve the aims, the study hypothesizes that: (1) there is no one-to-one correspondence between the structures of polite requests in English and their realization in Kurdish. (2) Kurdish makes use of markers of polite requests more than English does. (3) The illocutionary force of English polite requests the intended effect or function of the utterance can be translated in case the communicative translation is exploited. To test these hypotheses, the study adopts a qualitative research methodology utilizing Newmark’s (1988) approach to translation in terms of his distinction between semantic translation (word-for-word accuracy) and communicative translation (contextual and cultural effectiveness), as a framework to analyse 10 polite requests in English translated by 10 fourth-year students at the Dept. of Translation-College of Languages, University of Duhok. Translation Failure is also taken into consideration which is a text where the message transfer is inaccurate due to significant linguistic or pragmatic errors. The study concludes that polite markers which give the utterances the force of polite requests in Kurdish are more than those in English. Moreover, the differences in percentage, (79% semantic) and (17% communicative) and (4% failure) highlight that there is no one-to-one correspondence between the structures of polite requests in English and their realization in Kurdish